THE NORTHERN SEA ROUTE AND RUSSIAN STRATEGY - Donahue, Peter S. (Monterey, CA; Naval Postgraduate School, 2022)
The Northern Sea Route (NSR) has been important to Russian strategy since the 1930s. Climate change has increased average global temperature and caused sea ice to melt. Access to the NSR has been steadily increasing, creating new potential for the route. This thesis seeks to determine Russia’s primary aim for developing the NSR. It first analyzes Russia’s stated objectives for the NSR and identifies three main potential incentives: international transportation route development, natural resource development, and national security. Next, the thesis analyzes the actions that Russia has actually taken to develop the NSR in each of these categories. It finds that there is evidence to support both an economic incentive of natural resource development and a strategic incentive of national security development for the NSR. The thesis did not find support for the incentive of an alternate global trade route. The evidence suggests that Russia is taking steps to propel itself both economically and strategically on a global scale. The study recommends follow-on research to determine whether resource development or national security is more important to the Russian government. Approved for public release. Distribution is unlimited. Lieutenant, United States Navy